Bioguided study of the Antarctic alga Himantothallus grandifolius (A. Geep & E.S. Geep) indicates 13E-Docosenamide as potential antileishmanial agent - Clementino, Leandro Costa [UNESP]; Torres, Fabio Aurelio Esteves [UNESP]; Velasquez, Angela Maria Arenas [UNESP]; Villela, Leonardo; Mutue, Toyota Fujii; Colepicolo, Pio; Graminha, Marcia A.S. [UNESP] (SAGE Publications, 2020)
Constant efforts to discover new antileishmanial agents are important because there are only a few available drugs for the treatment of leishmaniasis, which present several drawbacks including high toxicity and difficult route of administration. In this scenario, different sources of natural products have been explored regarding their potential to treat infectious diseases. Following this initiative, our research team has been analyzing the bioactive potential of Himantothallus grandifolius, an endemic macroalga of the Antarctic region, with the hypothesis that the hostile environment imposed on these organisms has shaped its arsenal of chemical constituents, thus consequently bringing new opportunities to discover bioactive compounds that might be useful against leishmaniasis. Herein, we report the antileishmanial property of the fatty acid 13E-docosenamide, identified during the fractionation of the hexanic extract of H. grandifolius after semipreparative high performance liquid chromatography separation and ultrafast liquid chromatography coupled with mass spectrometry analyses to track its antileishmanial constituents. 13E-docosenamide was found in HSG11and HSG12 fractions, presented promising antileishmanial activity (IC50 = 9.6 μg ml-1) and is 10 times more selective to the parasite rather than to the host cells (SI > 10.4).
Keywords: 13E-docosenamide; antarctic macroalgae; antileishmanial activity; desmarestiaceae; fatty acid